2010
DOI: 10.12973/ejmste/75234
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on Proactive-Reactive Personality Profiles in Student-teacher Relationship through the Metaphorical Thinking Approach

Abstract: This study analyzed the proactive and reactive personality traits in teachers and students. These traits were interpreted with the help of the ideas and images revealed through metaphors. With the help of these metaphors, the certain imaginative categories and statements of student teachers about the teacher, the student and teacher-student relationship were associated with both reactive and proactive personality models. The sampling of the study involved 330 Biology, Physics and Chemistry track students at Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Findings of the study displayed that teachers related students to reactive personality, where passive behaviors are dominant, they related teachers to proactive personality, which indicates a tendency to start and continue and action on changing the environment directly (Şahin, 2006). Parallel to the conclusions of this study, some studies, where teacher and student concepts were questioned through metaphors Yücel, Koçak & Cula, 2010), concluded that reactiveness as one of the personality traits in the psychological pattern was found in students, while proactiveness was a trait for teachers. These common conclusions obtained in the studies would enlighten some factors that were avoided in the previous studies (Taylor, 1984).…”
Section: Conclusion and Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Findings of the study displayed that teachers related students to reactive personality, where passive behaviors are dominant, they related teachers to proactive personality, which indicates a tendency to start and continue and action on changing the environment directly (Şahin, 2006). Parallel to the conclusions of this study, some studies, where teacher and student concepts were questioned through metaphors Yücel, Koçak & Cula, 2010), concluded that reactiveness as one of the personality traits in the psychological pattern was found in students, while proactiveness was a trait for teachers. These common conclusions obtained in the studies would enlighten some factors that were avoided in the previous studies (Taylor, 1984).…”
Section: Conclusion and Discussionsupporting
confidence: 72%
“…Therefore, it is a common topic in the literature to analyze teachers' and teacher candidates' perceptions about teacher, student, school, principal and classroom concepts. A quick literature scan would result in studies on metaphors reflecting the perceptions on Teacher (Berman et.al., 2002;Cerit, 2008;Çelikten, 2005;Oxford et.al., 1998;Saban, 2004;Yücel & Koçak, 2008), Student (Saban, 2009;Tyson, 1995;Yücel, Koçak & Cula, 2010), School (Aydoğdu, 2008;Baker, 1991;Balci, 2001;Bayram, 2010;Mahlios & Maxson, 1998;Saban, 2008;Saban, Koçbeker &Saban, 2006;Yılmaz, 2011), Campus (Önen &Koçak, 2010), Chemistry (Koçak et.al., 2011), as well as courses such as Math and Geography (Gecit & Gencer, 2011;Güveli et.al., 2011;McColm, 2007;Öztürk, 2007).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second implication of the present study is that positive teacher-student relationships could positively influence academic engagement. According to this, maintaining strong teacher-student relationships is important, which requires teachers and students to mutually interact (Yücel et al, 2010 ). From the teachers' perspective, teachers should consider students' perspectives and negotiate with them, instead of holding absolute authority, to achieve educational goals and protect the proactive personality of students (Alderman and Green, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…pengalaman sehari-hari; 2) linking metaphors, yaitu membangun keterkaitan antara dua hal yaitu memilih, menegaskan, memberi kebebasan, dan mengorganisasikan karakteristik dari topik utama dengan didukung oleh topik tambahan dalam bentuk pernyataan-pernyataan metaforik; dan 3) redefinitional metaphors, yaitu mendefinisikan kembali metafor-metafor tersebut dan memilih yang paling cocok dengan topik yang akan diajarkan (Heris: 2017). Metafora memungkinkan individu untuk membandingkan fenomena abstrak atau kompleks dengan yang lebih konkrit atau berpengalaman dan mengembangkan pemahaman untuk fenomena yang tidak diketahui(Yucel, 2010). Peneliti meyakini bahwa penerapan pendekatan metaphorical thinking dapat dijadikan solusi untuk meningkatkan kemampuan penalaran matematis siswa.…”
unclassified